Ethnomusicology: A Study of its Nature, its Problems, Methods and Representative Personalities to which is Added a Bibliography - Kunst, Jaap 1891-1960 (The Hague Nijhoff, 1959)
This booklet hardly needs a preface; the contents, I think, speak for themselves. It contains a short and carefully brought up to date resume of all that I, as a private University Lecturer in Amsterdam, have tried to teach my pupils. It is intended as a general introduction to ethnomusicology, before going on to the study of the forms of separate music-cultures. I sincerely hope that those, who wish to teach themselves and to qualify in this branch of knowledge, will find a satisfactory basis for self tuition in the matter here brought together.
Keywords: Ethnomusicology